Efektivitas Program Beras Sejahtera dalam Meningkatkan Kesejahteraan masyarakat Pra Sejahtera di Kecamatan Ranoyapo Kabupaten Minahasa Selatan - Rumondor, Fraike; Lengkong, florence Daicy; Palar, Novie Anders (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Rice is a prosperous food subsidy in the form of rice earmarked for low-income households as theefforts of the government to improve food security and provide social protection to targeted households. Thesuccess of Rice Program prosperity is measured by the level of achievement 6T indicators, namely: the righttarget, the right amount, the right price, right time, right quality and right administration. The program aims toreduce the burden of Target Households spending through the partial fulfillment of staple food needs in theform of rice and prevent a decrease in consumption of energy and protein. The purpose of this study is toidentify the effectiveness of Rice Welfare Program in improving public welfare in the District Ranoyapo PreprosperousSouth Minahasa regency.Data collection techniques in this research is through: Observation namely direct observation to thestudy site, conduct interviews and documentation. Results of the evaluation showed that the program in theDistrict Ranoyapo prosperous rice was not effective because there are still some things that are not appropriateas the data receiver has not updated the program, the government is less involved mislead the public so thatpeople do not know clearly the price and the actual amount of rice. Likewise, there is a supplementary budgetthat is charged to the public for reasons of money transport vehicles rice and supervision of the districtgovernments are still lacking.Keywords: Program Effectiveness Rice Welfare, Welfare Pre prosperous society.